Determinants of demand for life insurance: The example of farmers from north-west Poland - Kurdyś-Kujawska, Agnieszka; Sompolska-Rzechuła, Agnieszka (Determinanty popytu na ubezpieczenie na życie: przykład rolników z regionu północno-zachodniej Polski, 2019)
Life insurance is a voluntary and additional element of protection and financial security for the future of insured and financially dependent persons. This safeguard should be of particular importance in the agricultural sector, which is characterized by a high number of accidents at work causing loss of health and death. The decision to buy life insurance depends largely on the economic and social factors characterizing the farm. The purpose of the article is to identify and evaluate the factors determining the purchase of life insurance by persons conducting agricultural activity. Data was collected in the north-west region of Poland using a survey questionnaire. Identification of the factors affecting the purchase of life insurance was made by means of a two-dimensional relationship analysis and logit regression model. The basis of the model was a set of obtained independent variables, based on a survey conducted in 2018 among randomly selected farm owners or managers. The analysis showed that the decision to buy life insurance depended on the sex of the farm owner or manager, the number of people in the farmer’s household, and possession of production insurance. The presented research results indicate that the probability of buying life insurance decreased when the owner or manager of the farm was a man. On the other hand, when the number of people in the farmer’s household increased and agricultural production was insured, the probability of buying life insurance increased. Research results suggest that having life insurance is associated with high awareness of the threats arising from farming activities and is an expression of ensuring financial security for the farmer’s family members in the future
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 71-81
Keywords: life insurance; farms; agricultural activity; financial security; logit model; ubezpieczenia na życie; gospodarstwa rolne; działalność rolnicza; bezpieczeństwo finansowe; model logitowy